Chimeric Glutamate Receptor Subunits Reveal the Transmembrane Domain Is Sufficient for NMDA Receptor Pore Properties but Some Positive Allosteric Modulators Require Additional Domains - Wilding, Timothy J. (J Neurosci, 2016)
NMDA receptors are ligand-gated ion channels that underlie transmission at excitatory synapses and play an important role in regulating synaptic strength and stability. Functional NMDA receptors require two copies of the GluN1 subunit coassembled with GluN2 (and/or GluN3) subunits into a heteromeric tetramer. A diverse array of allosteric modulators can upregulate or downregulate NMDA receptor activity. These modulators include both synthetic compounds and endogenous modulators, such as cis-unsaturated fatty acids, 24(S)-hydroxycholesterol, and various neurosteroids. To evaluate the structural requirements for the formation and allosteric modulation of NMDA receptor pores, we have replaced portions of the rat GluN1, GluN2A, and GluN2B subunits with homologous segments from the rat GluK2 kainate receptor subunit. Our results with these chimeric constructs show that the NMDA receptor transmembrane domain is sufficient to account for most pore properties, but that regulation by some allosteric modulators requires additional cytoplasmic or extracellular domains. SIGNIFICANCE STATEMENT Glutamate receptors mediate excitatory synaptic transmission by forming cation channels through the membrane that open upon glutamate binding. Although many compounds have been identified that regulate glutamate receptor activity, in most cases the detailed mechanisms that underlie modulation are poorly understood. To identify what parts of the receptor are essential for pore formation and sensitivity to allosteric modulators, we generated chimeric subunits that combined segments from NMDA and kainate receptors, subtypes with distinct pharmacological profiles. Surprisingly, our results identify separate domain requirements for allosteric potentiation of NMDA receptor pores by pregnenolone sulfate, 24(S)-hydroxycholesterol, and docosahexaenoic acid, three endogenous modulators derived from membrane constituents. Understanding where and how these compounds act on NMDA receptors should aid in designing better therapeutic agents.